RANCANG BANGUN SMART BOX PENERIMA PAKET EKSPEDISI MENGGUNAKAN WEMOS D1 R2 DAN QR CODE SCANNER - Arief Permana Putra; Diky Siswanto; Istiadi (JASEE Journal of Application and Science on Electrical Engineering, 2025)
Online shopping increases the need for a package receiving system that can operate when the recipient is not at home. This study aims to design and test an Internet of Things-based smart package receiving box using Wemos D1 R2, a QR Code scanner, a fingerprint sensor, solenoid door locks, and a web server. The system allows users to register package receipt numbers through a web interface. Couriers can open the package entry door by scanning a registered receipt code, while users can retrieve the package through fingerprint authentication. System testing was conducted on three main functions: receipt number registration to the database, QR Code-based package access, and fingerprint-based user access. The receipt number registration test showed that all five trials were successfully stored in the database, with a response time range of 2–3 seconds and an average of 2.4 seconds. QR Code validation activated the solenoid lock in all five trials. Fingerprint authentication also succeeded in all five trials under clean finger conditions, with an average door-opening response time of 5 seconds. These results indicate that the proposed prototype can support automatic package reception with controlled access, although wider testing under real delivery and network conditions is still required.